Differential interference effects of negative emotional states on subsequent semantic and perceptual processing - Sakaki, Michiko (2011)
Past studies have revealed that encountering negative events interferes with cognitive processing of subsequent stimuli. The present study investigated whether negative events affect semantic and perceptual processing differently. Presentation of negative pictures produced slower reaction times than neutral or positive pictures in tasks that require semantic processing, such as natural/man-made judgments about drawings of objects, commonness judgments about objects, and categorical judgments about pairs of words. In contrast, negative picture presentation did not slow down judgments in subsequent perceptual processing (e.g., color judgments about words, and size judgments about objects). The subjective arousal level of negative pictures did not modulate the interference effects on semantic/perceptual processing. These findings indicate that encountering negative emotional events interferes with semantic processing of subsequent stimuli more strongly than perceptual processing, and that not all types of subsequent cognitive processing are impaired by negative events.